2022
DOI: 10.1186/s12888-022-04236-z
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the association of anxiety and depression with the disease activity of systemic lupus erythematosus

Abstract: Background Systemic Lupus Erythematosus (SLE) is an autoimmune disease that affects multiple systems and increases the risk of mental disorders such as depression and anxiety. We conducted an observational, single-center, cross-sectional study to investigate the relationship between depression, anxiety, and SLE disease activity. Methods The Patient Health Questionnaire 9 (PHQ-9) was used to assess depression, and the 7-item Generalized Anxiety Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…22 Four epidemiological studies have assessed psychiatric comorbidities in patients with SLE as per the DSM-IV or DSM IV-TR, and the prevalence rate of the current study is comparable with these studies. [22][23][24][25] In the present study, the total number of individuals who screened positive for moderate, moderately severe and severe depression on PHQ-9 was approximately 39.8%, which corroborated with the clinically identified prevalence of depressive disorder in the group. We could not find any other study which attempted to assess patients of SLE for psychiatric based both on clinical interview and a validated screening instrument.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…22 Four epidemiological studies have assessed psychiatric comorbidities in patients with SLE as per the DSM-IV or DSM IV-TR, and the prevalence rate of the current study is comparable with these studies. [22][23][24][25] In the present study, the total number of individuals who screened positive for moderate, moderately severe and severe depression on PHQ-9 was approximately 39.8%, which corroborated with the clinically identified prevalence of depressive disorder in the group. We could not find any other study which attempted to assess patients of SLE for psychiatric based both on clinical interview and a validated screening instrument.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study used PHQ-9 as a screening tool for depression in SLE, and reported similar prevalence. 25 On PHQ-15, 17.7% of the participants scored for a severe somatic distress (score >15). We could not find any previous study attempting to quantify the somatic distress of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses suggest that the overall prevalence of depression and anxiety among SLE patients is 35%, respectively 25.8%, with ranges from 8.7% to 78.6% for depression and from 1.1% to 71.4% for anxiety, but the authors emphasize that the heterogeneity of the assessment’s scales used for these two majors neuropsychiatric SLE manifestations make challenging to identify a precise prevalence of anxiety and depression among SLE patients [ 9 ]. At the same time recent cross-sectional research results on SLE patients showed depression in 61.5% of patients and anxiety in 54.4% and suggested a cut-off value for SLEDAI of 8.5 for the increased risk of neuropsychiatric SLE manifestations [ 37 ]. This research indicates a strong correlation between depression symptoms and severe disability in social participation, interpersonal relationships and life abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychiatric symptoms of SLE are the most complex and severe manifestations of the disease, 17 with major depression being one of the most common manifestations and positively correlated with the disease activity index. 14,18 A growing…”
Section: Discussionmentioning
confidence: 99%